Communicative Competence: Its Implications for English-as-a-Foreign-Language Teachers in Indonesia - Faisal Faisal (Universitas Muhammadiyah Surakarta, 2025)
This paper forms part of a broader study investigating the competencies required of secondary-school English teachers and the implications of communicative competence for teaching English as a foreign language (TEFL) within the Indonesian context, as emphasized in national curriculum documents. Employing a document analysis methodology, the study examines these curriculum frameworks to identify key implications for English language teachers at the secondary level in Indonesia. The findings highlight essential considerations for instructional practices, including an emphasis on fluency, student-centered learning, and communicative-based approaches. Specifically, the study suggests that English teachers in Indonesia should prioritize fluency over accuracy, adopt student-centered pedagogies, and integrate communicative strategies to facilitate effective language acquisition and help students achieve desired learning outcomes. By enhancing the understanding of TEFL practices in Indonesia, this study offers valuable insights for English language educators in designing effective teaching programs that align with the competencies outlined in the national curriculum.